The right-brain alternative - Zheleznyak, Olga (project baikal, 2023)
The era of left-brain dominance is beginning to give way to a new world in which right-brain ideals prevail and creativity is valued. Being a kind of opposition to the information age, they become a response to the challenges of the right-brain thinking age and drivers of development, presenting right-brain skills as most relevant to life and business. Creative industries/economies/professions are increasingly in demand as an alternative to the “classical” industry, as creativity provides a competitive advantage by adding value to a service or product.
Keywords: right-brain thinking; creativity; creative industries; creative economies; creative professions